Ameloblastic fibro-odontoma in an unusual area of the maxilla: Two Case Reports. - Daniela Valencia; Elio Jiménez; Samuel Urbano (Universidad de Concepción., 2019)
Ameloblastic fibro-odontoma (AFO) is a mixed odontogenic tumor, which has an epithelial and mesenchymal component. It can be observed in imaging tests as a radiomixed lesion, with some authors claiming it represents only the predecessor of an odontoma. Epidemiologically, it appears between the second and third decade of life, predominantly in males and with a predilection for the posterior area of the mandible. This lesion presents a good prognosis and it responds well to enucleation by curettage with a low rate of recurrence. In the present article, two cases of ameloblastic fibro-odontoma in an unusual region of the maxilla are presented.